2019
DOI: 10.1177/1329878x19853074
|View full text |Cite
|
Sign up to set email alerts
|

From contempt of court to fake news: public legitimisation and governance in mediated Singapore

Abstract: Common perceptions and literature on media in Singapore suggest an authoritarian government that either silences or co-opts public media, using repressive laws that are passed unopposed, given the People’s Action Party (PAP) government’s super majority in Parliament. In practice, laws in Singapore are not simply crafted to maximise their effects in silencing political criticism but are also carefully debated – at times with the PAP’s strongest opponents – in public, to rationalise their implementation even bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Previous research has suggested that targeted messaging and intervention may be more effective when introduced through a family doctor ( 54 ), grassroots volunteers from the community using a multi-component approach [i.e., home visits, telephone and leaflets reminders; ( 71 , 72 )], and through traditional media such as television and newspapers ( 73 ). Further, as older adults may be more susceptible to misinformation ( 74 , 75 ), establishing that messages through said channels are verified—whether through government ( 76 ) or journalist intervention ( 77 )—and education on digital literacy ( 78 , 79 ) may serve as potential counters.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that targeted messaging and intervention may be more effective when introduced through a family doctor ( 54 ), grassroots volunteers from the community using a multi-component approach [i.e., home visits, telephone and leaflets reminders; ( 71 , 72 )], and through traditional media such as television and newspapers ( 73 ). Further, as older adults may be more susceptible to misinformation ( 74 , 75 ), establishing that messages through said channels are verified—whether through government ( 76 ) or journalist intervention ( 77 )—and education on digital literacy ( 78 , 79 ) may serve as potential counters.…”
Section: Discussionmentioning
confidence: 99%
“…For the most part, this is due to the structure and dynamics of Singaporean society, and its political arrangements, public policy traditions and strong systems of social control and clear support for or alternatively discouragement and sanctioning of different kinds of expression and voicessomething well established in the scholarly literature (Chua, 2017;George, 2000George, , 2017Lee, 2010Lee, , 2014, especially via various studies published in Media International Australia (most recently, Lee and Lee, 2019). In recent years, the Singapore government, following the dampened level of votes received by governing People's Action Party (PAP), that has ruled since the 1967, in the 2011 Election, and a more sceptical populace (Barr, 2016;Zhang, 2016), it has sought to extend consultation and formal 'listening' mechanisms to provide additional opportunities for citizens' voices.…”
Section: Singapore's Tracetogether: 'A Fair Degree Of Privacy'mentioning
confidence: 99%
“…Mcnair (2017) coined ‘media management’ as a way in which the state operates, shapes, and pressures media organizations to align with the government’s political perspectives. Co-optive practices of the media refer to the ways authoritarian states co-opt public media institutions by adopting a variety of strategies (legal, political, and social) to retain political stronghold (Lee and Lee, 2019). This may not always entail the use of repressive laws, but through sophistry in governmentality by ‘convincing the citizenry to consent the suppression of their own socio-cultural and political freedom’ (Lee and Lee, 2019: 1).…”
Section: Migrant Domestic Workmentioning
confidence: 99%